A Smart Campus Communication System - M.R, Kruthika; Kumar N.S, Adithya; Abhishek, S; Abhigna, A (International Journal of Computer Sciences and Engineering, 2025)
Notices, posters, digital panels, social media, and emails are the various means of communication within a campus today. Existence of multiple means leads to confusion and the information to be delivered can be missed or forgotten. To address this issue, we aim to create a steadfast workflow that will enable the individuals pertaining to an institution connect with one an-other, share information and participate in various events in a timely and a smart manne.